Nano Online 2016
DOI: 10.1515/nano.11671_2015.50
|View full text |Cite
|
Sign up to set email alerts
|

An Ingenious Super Light Trapping Surface Templated from Butterfly Wing Scales

Abstract: Based on the super light trapping property of butterfly Trogonoptera brookiana wings, the SiO 2 replica of this bionic functional surface was successfully synthesized using a simple and highly effective synthesis method combining a sol-gel process and subsequent selective etching. Firstly, the reflectivity of butterfly wing scales was carefully examined. It was found that the whole reflectance spectroscopy of the butterfly wings showed a lower level (less than 10 %) in the visible spectrum. Thus, it was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Interestingly, in the butterflies, these principles are being applied in a layer that is only 1/5th the thickness of synthetic or other natural materials. Similar to other work, we find that the nano-holes are crucial for reducing reflection by absorbing light that is channeled into the holes 7,9,13 . However, previous modeling of ultra-black butterfly scales has only included the ridges, holes, and upper and lower lamina of the scale, neglecting the trabeculae 13 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, in the butterflies, these principles are being applied in a layer that is only 1/5th the thickness of synthetic or other natural materials. Similar to other work, we find that the nano-holes are crucial for reducing reflection by absorbing light that is channeled into the holes 7,9,13 . However, previous modeling of ultra-black butterfly scales has only included the ridges, holes, and upper and lower lamina of the scale, neglecting the trabeculae 13 .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, it has been shown that several animals have evolved micro-or nanostructures that reflect as little as 0.05% of visible light, even at normal incidence [7][8][9][10][11] . Several species of birds of paradise have evolved complex barbule microstructures that increase light scattering and, consequently, the number of opportunities for light absorption by melanin embedded within the feather 10 .…”
mentioning
confidence: 99%
“…Based on a study of a new mechanism of behavioral thermoregulation, Kingsolver (1985) suggested that Pieris butterflies use their predominantly white wings as solar reflectors to reflect solar radiation onto the body and to increase their body temperature. Some studies also indicate that butterflies rely on "photonic crystal" structures in their wings to absorb heat (Li et al, 2004;Han et al, 2013;Luohong, 2014;Han et al, 2015a). Therefore, the transfer of heat in a butterfly not only depends on reflection and absorption from the wing surface, but it also is due to the internal tissue in the wing.…”
Section: Introductionmentioning
confidence: 99%
“…Kingsolver (1985) suggested that the wings act as solar reflectors in Pieris butterflies to reflect solar radiation onto the body in order to increase its temperature. However, some studies have shown that the absorption of heat by butterfly wings depends mainly on the internal structure of the scale itself, where the structure called a "photonic crystal" can convert the absorbed light into heat for autonomous flight (Li et al, 2004;Han et al, 2013;Luohong, 2014;Han et al, 2015a, b). In the butterfly Trogonoptera brookiana, the scales have longitudinal ridges that run through the scales and the surfaces of the scales comprises a set of raised longitudinal quasiparallel lamellae (ridges), where the spaces between adjacent ridges are filled with a netlike reticulum comprising pores (Han et al, 2015a).…”
Section: Heat Storage and Transfer In The Wingmentioning
confidence: 99%
“…Based on a study of a new mechanism of behavioral thermoregulation, Kingsolver (1985) suggested that Pieris butterflies use their wings as solar reflectors to reflect solar radiation onto the body and to increase their body temperature. Some studies also indicate that butterflies rely on "photonic crystal" structures in their wings to absorb heat (Li et al, 2004;Han et al, 2013;Luohong, 2014;Han et al, 2015a). Therefore, the transfer of heat in a butterfly not only depends on reflection from the wing surface, but it also is due to the internal tissue in the wing.…”
Section: Introductionmentioning
confidence: 99%